2019
DOI: 10.1177/2158244019859087
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effects of Religiosity on the Relationship Between Trauma and Suicidal Behaviors Among College Students in Northwest China

Abstract: Studies have shown that traumatic experiences are positively associated with risk of suicidal behaviors, whereas religiosity has been found to be negatively associated with that risk. How exactly religiosity interacts with traumatic experiences in its relationship to suicidal behaviors remains unclear. The current study examined the moderating effects of religiosity on the relationship between traumatic experiences and suicidal behaviors in 5,301 college students in northwestern China. Results indicated a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…Data from an Israeli population-based sample support these theoretical assertions, demonstrating that lifetime suicide attempts, though not suicidal ideation, were significantly less common in religious individuals than non-religious individuals independent of substance use, psychopathology, and social functioning (Burshstein et al, 2016). A similar pattern was found in a sample of college students in northwestern China, where greater religiosity was associated with a reduced risk of suicidal behaviors following traumatic experiences (He et al, 2019).…”
Section: Introductionsupporting
confidence: 77%
“…Data from an Israeli population-based sample support these theoretical assertions, demonstrating that lifetime suicide attempts, though not suicidal ideation, were significantly less common in religious individuals than non-religious individuals independent of substance use, psychopathology, and social functioning (Burshstein et al, 2016). A similar pattern was found in a sample of college students in northwestern China, where greater religiosity was associated with a reduced risk of suicidal behaviors following traumatic experiences (He et al, 2019).…”
Section: Introductionsupporting
confidence: 77%
“…Data from an Israeli population‐based sample demonstrated that lifetime suicide attempts, though not suicidal ideation, were significantly less common in religious individuals than non‐religious individuals independent of substance use, psychopathology, and social functioning (Burshtein et al., 2016). A similar pattern was found in a sample of college students in northwestern China, where greater religiosity was associated with a reduced risk of suicidal behaviors following traumatic experiences (He et al., 2019). Nevertheless, more work is needed to determine if religious contexts provide unique buffers against interpersonal risk factors for suicide, as one study found that secular “churches” offer comparable social connectedness to their religious counterparts (Brown et al., 2021).…”
Section: Introductionsupporting
confidence: 75%
“…For example, other authors have found that religiosity acted as a moderator of the association of traumatic stress with students' mental health. Under conditions of traumatic stress, religiosity was associated with positive reappraisal of stress, better mental health and posttraumatic growth in university students (He et al, 2019). Under difficult life circumstances, religiosity has reduced the effects of stress and has led to higher subjective well-being, but under regular stress, religiosity did not have such a positive impact on the relationship between stress and life satisfaction (Kim-Prieto & Miller, 2018).…”
Section: Discussionmentioning
confidence: 99%